Influence of spermatozoal lipidomic profile on the cryoresistance of frozen spermatozoa from stallions - Cabrera, T. [UNESP]; Ramires-Neto, C. [UNESP]; Belaz, K. R.A.; Freitas-Dell'aqua, C. P. [UNESP]; Zampieri, D.; Tata, A.; Eberlin, M. N.; Alvarenga, M. A. [UNESP]; Souza, F. F. [UNESP] (Elsevier, 2018)
The membrane of spermatozoa, which contributes to cellular cryoresistance, contains numerous lipids with a composition that directly affects membrane fluidity and the fertilization process. In light of variations in the degree of sensitivity in equine seminal freezing, this study aimed to correlate equine semen lipids with post-thawing characteristics of spermatozoa. We used ejaculates from 34 stallions, which were evaluated (total motility ≥ 60%), frozen and thawed and reevaluated for motility of spermatozoa, membrane integrity and lipid peroxidation. Lipid extraction of the fresh semen samples was performed by liquid-liquid extraction, and fingerprinting lipid analysis was conducted by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). Based on the characteristics of spermatozoa after thawing, the animals could be separated into two groups: resistant (Good Freezers, n = 5) and sensitive (Bad Freezers, n = 6) to freezing, and their MALDI-MS data were then compared. The Good Freezers group showed a higher abundance of phosphatidylcholines (m/z 796.6, 846.6, 810.6, 854.6 and 732.6). The ions of m/z 812.6, 832.6, 836.6 and 838.6 belonging to the phosphatidylcholine lipid class were also positively correlated with motility of spermatozoa, whereas that of m/z 794.6 was negatively correlated with lipid peroxidation in thawed semen. The Bad Freezer group, displayed higher abundance of one phosphatidylcholines (m/z 806.6), as well as a sphingomyelins (m/z 703.5), which were negatively correlated (univariate analysis) with kinetics of spermatozoa after thawing (m/z 703.5) and with membrane integrity (m/z 792.6). The ion of m/z 717.5, assigned to phosphatidic acid, was negatively correlated with lipid peroxidation. In general therefore, the phosphatidylcholines are associated with higher quality of spermatozoa after thawing, especially in functional capacity, and that lipid semen composition was found to influence the resistance of spermatozoa to cryopreservation and may interfere with motility, membrane integrity and lipid peroxidation in stallions.
Keywords: Equine; Freeze-semen; Lipid-profile; Mass spectrometry; Spermatozoa